Highly Efficient CO2 Electroreduction on ZnN4‐based Single‐Atom Catalyst. Issue 38 (23rd August 2018) - Yang, Fa; Song, Ping; Liu, Xiaozhi; Mei, Bingbao; Xing, Wei; Jiang, Zheng; Gu, Lin; Xu, Weilin
Abstract: The electrochemical reduction reaction of carbon dioxide (CO2RR) to carbon monoxide (CO) is the basis for the further synthesis of more complex carbon‐based fuels or attractive feedstock. Single‐atom catalysts have unique electronic and geometric structures with respect to their bulk counterparts, thus exhibiting unexpected catalytic activities. A nitrogen‐anchored Zn single‐atom catalyst is presented for CO formation from CO2RR with high catalytic activity (onset overpotential down to 24 mV), high selectivity (Faradaic efficiency for CO (FECO ) up to 95 % at −0.43 V), remarkable durability (>75 h without decay of FECO ), and large turnover frequency (TOF, up to 9969 h −1 ). Further experimental and DFT results indicate that the four‐nitrogen‐anchored Zn single atom (Zn‐N4 ) is the main active site for CO2RR with low free energy barrier for the formation of *COOH as the rate‐limiting step. Abstract : A nitrogen‐anchored Zn single‐atom catalyst is presented for CO formation from CO2RR with high catalytic activity (onset overpotential down to 24 mV), high selectivity (Faradaic efficiency for CO (FECO ) up to 95 % at −0.43 V), remarkable durability (>75 h without decay of FECO ), and large turnover frequency (TOF, up to 9969 h −1 ).